FAST TRACK LEGISLATION WITHOUT A LEGAL TRACK: A COMPARATIVE CRITIQUE OF ACCELERATED LAW-MAKING IN INDONESIA AND OTHER JURISDICTIONS - Kaharuddin Kaharuddin; Oemar Moechthar; Agus Sekarmadji; Dinar Karunia; Dwi Rahayu Kristianti; Ekawestri Prajwalita Widianti; Ave Maria Frisa Katherina; Yogi Hidayat (Fakultas Hukum, Universitas Diponegoro, 2025)
This study critically examines the trend of